2014
DOI: 10.1007/s10162-013-0435-7
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception in Noise with a Harmonic Complex Excited Vocoder

Abstract: A cochlear implant (CI) presents band-pass-filtered acoustic envelope information by modulating current pulse train levels. Similarly, a vocoder presents envelope information by modulating an acoustic carrier. By studying how normal hearing (NH) listeners are able to understand degraded speech signals with a vocoder, the parameters that best simulate electric hearing and factors that might contribute to the NH-CI performance difference may be better understood. A vocoder with harmonic complex carriers (fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Others have constructed more elaborate vocoders where the current spread was simulated using a simple model of electrical flow in the cochlear fluid (Bingabr et al, 2008;Churchill et al, 2014;Laneau et al, 2006). However, these approaches are limited by the fact that the relationship between the level of current in the cochlea and its specific contribution to loudness is unknown.…”
Section: Experiments 3: Effect Of Spread Of Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have constructed more elaborate vocoders where the current spread was simulated using a simple model of electrical flow in the cochlear fluid (Bingabr et al, 2008;Churchill et al, 2014;Laneau et al, 2006). However, these approaches are limited by the fact that the relationship between the level of current in the cochlea and its specific contribution to loudness is unknown.…”
Section: Experiments 3: Effect Of Spread Of Excitationmentioning
confidence: 99%
“…For comparison, Bingabr et al (2008) reviewed the literature for current spread estimates and reported an average value of 2.8 dB/ mm, which corresponds to slopes of about À40 dB/octave according to their calculation. Similarly, Churchill et al (2014) used filters with slopes ranging from À40 to À30 dB/ octave.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…It is worth noting that the filters which led to a plateau of performance in the present study (MP and BP þ 1) had bandwidths in between the medium and broad conditions of Bingabr et al, and that they led to a similar plateau. Recently, several vocoder studies have also used synthesis filter shapes similar to those of Bingabr et al in order to simulate the spread of excitation produced by a CI (Churchill et al, 2014;Stafford et al, 2014). Strydom and Hanekom (2011a) followed a different approach.…”
Section: Discussionmentioning
confidence: 98%
“…We use the term acoustic richness instead of vocal quality to emphasize that changes to acoustic detail of the speech signal can arise from many sources. Although many behavioral studies have assessed speech perception by systematically manipulating voice quality (Chen and Loizou, 2011, 2010; Churchill et al, 2014; Loizou, 2006; Maryn et al, 2009), relatively little neuroimaging research has investigated the neural consequence of acoustic richness in intelligible speech. Here we examine how acoustic clarity affects the neural processing of intelligible speech.…”
Section: Introductionmentioning
confidence: 99%